NEW TEACHING MATHEMATICS TEACHING EFFECTIVENESS OF THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Boshanqyzy, Zhanys Aray; Nurkasymovna, Nurkasymova Saule (International Journal of Research -GRANTHAALAYAH, 2017)
The possibilities of computer technologies in improving the quality of teaching mathematics and its application in the 7th grade students studied the impact on the development of mathematical thinking. Teachers and pupils kanşalıktı methodology to apply this technology meñgergendikteri tested and determined to improve the methods of teaching mathematics in the scientific literature of the main ideas, 7th grade, based on the best practices in the teaching of mathematics and taking into account the requirements set by the company’s mastery of mathematical concepts and rules and reports identified the role of the computer in teaching and service, including through the effective use of the computer are determined based on the study of the material should be studied.